2021
DOI: 10.1038/s41598-021-99400-y
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a neural network for NAFLD diagnosis

Abstract: Non-Alcoholic Fatty Liver Disease (NAFLD) affects about 20–30% of the adult population in developed countries and is an increasingly important cause of hepatocellular carcinoma. Liver ultrasound (US) is widely used as a noninvasive method to diagnose NAFLD. However, the intensive use of US is not cost-effective and increases the burden on the healthcare system. Electronic medical records facilitate large-scale epidemiological studies and, existing NAFLD scores often require clinical and anthropometric paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Future investigations could also incorporate additional preprocessing steps ( 31 ) , stain normalization on Sirius-Red stained images ( 27 ) , and extend the model to multi-class classification. We could also consider multimodal learning, since reasonable NAFLD diagnosis performance has been reported using DL on non-imaging data ( 36 , 37 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Future investigations could also incorporate additional preprocessing steps ( 31 ) , stain normalization on Sirius-Red stained images ( 27 ) , and extend the model to multi-class classification. We could also consider multimodal learning, since reasonable NAFLD diagnosis performance has been reported using DL on non-imaging data ( 36 , 37 ) .…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, numerous works have shown how ML or e-health tools are considered various alternatives to standard diagnostic methods [10][11][12][13] such as Magnetic Resonance Imaging (MRI), ultrasounds, etc. ML approaches are already used for NAFLD diagnosis [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that non-alcoholic fatty liver disease (NAFLD) is a clinicopathological condition that encompasses a variety of chronic liver diseases ranging from asymptomatic hepatic fat accumulation to progressive liver disease, with clinical symptoms resembling alcoholic liver disease despite the absence of excessive alcohol consumption 4 , 5 . A recent study revealed that the prevalence of NAFLD diagnosed by ultrasound was estimated to be about 25% 6 . It is estimated that either NAFLD or non-alcoholic steatohepatitis (NASH) will be the most common indication for liver transplantation by 2030 7 .…”
Section: Introductionmentioning
confidence: 99%